'Monkey Forest' Board Game: A Dynamic Tool for Young Learners to Learn English Sentence Structure - Parawansah, Salsa Bella; Sari, Valentina Dyah Arum (Jurnal Basicedu, 2024)
According to the curriculum, Elementary school students have to learn English sentence structure as a part of writing skill mastery. The challenge aroused when the students found the English pattern was different from Indonesian sentence structure. The students who are categorized as young learners need the appropriate strategy accommodating their characteristics. This research aimed to reveal the implementation and the benefits of Monkey Forest board game as a dynamic tool for young learners at one of the state elementary schools in Ngluwar, Central Java. This research used mixed-methods research. The instruments for obtaining data were questionnaires and interviews. The participants were 15 fifth graders. The research findings revealed that the implementation reached 72% showing medium qualifications. It revealed that the students gave positive responses to the implementation of Monkey Forest board game to learn English sentence structure. Besides, students' responses to the benefits of the Monkey Forest board game showed medium qualifications as well by obtaining 74.9%. Moreover, Monkey Forest board game as a dynamic tool to learn English sentence structure was evidenced to provide benefits to the students